2020
DOI: 10.3390/ijms22010213
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Cure: Targets and Future Therapies

Abstract: Chronic hepatitis B virus (HBV) infection is a major global health problem. It can cause progressive liver fibrosis leading to cirrhosis with end-stage liver disease, and a markedly increased risk of hepatocellular carcinoma. In the last two decades, substantial progress has been made in the treatment of chronic hepatitis, B. However, HBV is often reactivated after stopping nucloes(t)ide analogues because antivirals alone do not directly target covalently closed circular DNA, which is the template for all vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Such effectors would act on the assembled capsids before envelopment in contrast to the established capsid assembly modulators [56]. This is a still unexplored mode of action for HBV antivirals [6], and we believe that exploiting this potential may lead to developing new therapeutics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such effectors would act on the assembled capsids before envelopment in contrast to the established capsid assembly modulators [56]. This is a still unexplored mode of action for HBV antivirals [6], and we believe that exploiting this potential may lead to developing new therapeutics.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic carriers rely on antivirals, which interfere with the viral maturation cycle to control their viral load. Some antivirals target the virus assembly and are now under clinical trials (for review, see [5,6]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the consensus in the field is that drugs will have to be used in combination in order to achieve an HBV cure. New therapeutic approaches and the results of preclinical/clinicals trials have been discussed in recent reviews [ 107 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HBV infection accounts for approximately 80% of virus-associated HCC cases and virtually all of childhood HCC, especially in Africa and East Asia, while HCV infection, involved in about 20% of the total HCC cases, seems to be mainly related to HCC development in Western Europe and North America [91]. Prospective cohort studies have shown a significant increase in the risk of developing HCC among persons chronically infected with HBV or HCV [91,93]. Between 70 and 90% of the HBV-infected individuals who develop HCC have cirrhosis secondary to chronic necroinflammation [91,93].…”
Section: Viral Hepatitismentioning
confidence: 99%
“…Prospective cohort studies have shown a significant increase in the risk of developing HCC among persons chronically infected with HBV or HCV [91,93]. Between 70 and 90% of the HBV-infected individuals who develop HCC have cirrhosis secondary to chronic necroinflammation [91,93]. HCV also increases the risk of HCC by inducing fibrosis and, eventually, cirrhosis [91].…”
Section: Viral Hepatitismentioning
confidence: 99%